Intussusception in A Neonate: A Rare Clinical Entity - Zafar, Anam; Riaz, Noshina; Naz, Farah; Ghazi, Shahzadi Sumbal; Akhtar, Saima (Pakistan Armed Forces Medical Journal, 2025)
Intussusception is defined as invagination of bowel segment into its distal portion causing intestinal obstruction. It is rarely seen in neonates, accounting for 0.3% among all cases. Classical signs of intussusception are hardly seen in neonatal age group leading to delayed or misdiagnosis. We report a case of intussusception in full term neonate who presented with clinical picture of neonatal sepsis, developed intestinal obstruction secondary to ileocolic intussusception. However, in our case patient succumbed to death due to overt sepsis. Very few publications are found about intussusception in neonates in the last few decades and most of them are case reports, highlighting the scarcity of available data.